Alasan Pemaaf pada Undang-Undang No 36 Tahun 2009 tentang Kesehatan terhadap Pelaku Aborsi ditinjau dari Hukum Islam - Rengga Saputra; Jerry Pratama (Journal of Islamic Law and Wisdom, 2025)
This study examines the excusing reasons for individuals who perform abortions as regulated by Law No. 36 of 2009 on Health, from the perspective of Islamic law. The background of the problem stems from differing interpretations of abortion’s legality between Indonesian positive law and Islamic legal principles, particularly regarding exceptions for medical emergencies and rape. The novelty of this research lies in its comparative approach, which analyzes the similarities and differences between the abortion provisions in the Health Law and the views of Islamic law, as well as the relationship between national policy and religious fatwās. The research methodology is normative juridical, employing library research with primary data drawn from legislation (the Criminal Code; Law No. 36/2009) and Islamic sources (the Qur’ān, Hadith, fatwās), and secondary data comprising academic literature and prior studies. The main findings indicate that both legal systems permit abortion under emergency conditions (to save the life of the mother or fetus), but differ in gestational age limits; technical regulations and the legal status of abortions resulting from rape also diverge, with scholars holding varying opinions.